2017
DOI: 10.3389/fneur.2017.00167
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Phenylketonuria: An Explorative Study in Men and Mice

Abstract: Sleep problems have not been directly reported in phenylketonuria (PKU). In PKU, the metabolic pathway of phenylalanine is disrupted, which, among others, causes deficits in the neurotransmitters and sleep modulators dopamine, norepinephrine, and serotonin. Understanding sleep problems in PKU patients may help explain the pathophysiology of brain dysfunction in PKU patients. In this explorative study, we investigated possible sleep problems in adult treated PKU patients and untreated PKU mice. In the PKU patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Of the 643 articles retrieved from the initial search, 83 met criteria for inclusion in this review (Figure ). Patients had been maintained on a Phe‐restricted diet during early childhood, although this did not necessarily equate to strict treatment; overall adherence to diet throughout their lifetime was not consistently reported and was variable between studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 643 articles retrieved from the initial search, 83 met criteria for inclusion in this review (Figure ). Patients had been maintained on a Phe‐restricted diet during early childhood, although this did not necessarily equate to strict treatment; overall adherence to diet throughout their lifetime was not consistently reported and was variable between studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study did find that patients with PKU experienced only internalizing disturbances (emotional problems such as depression and anxiety), while healthy controls exhibited both internalizing and externalizing disturbances (interpersonal problems such as antisocial behavior) equally . Regarding sleep behavior, one study reported that adult patients with ETPKU presented more sleep disorders, reduced sleep quality, increased latency to fall asleep, and more daytime sleepiness compared with first degree relatives …”
Section: Psychiatric Mood and Behavioral Outcomesmentioning
confidence: 99%
“…All patients showed subjectively good sleep quality, 15 very good and 10 fairly good. By contrast, Bruinenberg et al, 19 found more sleep disorders (specially insomnia and circadian rhythm sleep disorders) and reduced sleep quality in 25 treated adult PKU patients (mean age: 30 ± 9) compared to controls, but they did not assess metabolic control or provide the age when treatment was started in these patients. Bilder et al, 18 reported a sleep disorder prevalence of 14.4% in 3714 adult PKU patients (aged 20 to >80 years, mean age: 38.5 years) versus 6.9% in general population controls, which fell to 9% in the age range of 20e39 years (n ¼ 2247) (the authors supposed that this adult cohort were most likely to have had early and continuous treatment).…”
Section: Discussionmentioning
confidence: 90%
“…6,15 Regarding the serotoninergic deficit, references to its repercussions on sleep quality have been described in the literature but are scarce, 16 even studies in which sleep is evaluated. In that sense, our group has performed a previous study in early-treated PKU young adult patients in which alterations in sleep quality were not found 17 ; however, recent studies have been published in PKU adults 18,19 reporting more sleep disorders than in controls.…”
Section: Introductionmentioning
confidence: 97%
“…In turn, this neurotransmitter deficiency is associated with depression (serotonin deficiency) and behavioural disturbances (especially frontal lobe dysfunction in dopamine deficiency) [ 35 ]. Sleep disturbances in PKU patients have been also well documented [ 11 ]. Bioavailability of tyrosine due to changes in intestinal microbiota and altered metabolism of tryptophan via the kynurenine pathway in patients who are ingesting medical foods also contribute to the bioamine defects [ 32 ].…”
Section: Introductionmentioning
confidence: 99%